2017
DOI: 10.5455/msm.2017.29.216-218
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hygiene Habits in Acrylic Denture Wearers: a Cross-sectional Study

Abstract: Objectives:To assess the denture hygiene habits in a population of Lebanese denture wearers.Materials and Methods:One hundred and thirty-two (132) patients [71 women (53.8%) and 61 men (46.2%)] wearing their acrylic dentures for more than two years were included in this study. The hygiene methods related to their dentures were evaluated and the data obtained were analyzed statistically using the IBM® SPSS® statistics 20.0 (USA) statistical package.Results:Regardless of the cleaning technique, the big majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…19,20 Mushtaq et al in his study showed that 57.3% of patients received instruction from their dentists or dental staff whereas Aoun et al from his study revealed that 43 of 200 participants received instructions regarding denture cleaning protocol. 3,4 The limitations of this study are that the subjects participating in the research belong to a localized population and there has been no correlation between hygiene habits, age, education level, and status of the patient. Another limitation of this study is that the status of denture-bearing soft tissue has not been scored.…”
Section: How Do You Clean Your Dentures?mentioning
confidence: 98%
See 2 more Smart Citations
“…19,20 Mushtaq et al in his study showed that 57.3% of patients received instruction from their dentists or dental staff whereas Aoun et al from his study revealed that 43 of 200 participants received instructions regarding denture cleaning protocol. 3,4 The limitations of this study are that the subjects participating in the research belong to a localized population and there has been no correlation between hygiene habits, age, education level, and status of the patient. Another limitation of this study is that the status of denture-bearing soft tissue has not been scored.…”
Section: How Do You Clean Your Dentures?mentioning
confidence: 98%
“…1,3 The microporous nature of acrylic denture base provides the ideal environment to colonize microorganisms including bacteria and fungi, resulting in a tenacious biofilm leading to oral tissue diseases and serious systemic ailments. 1,4 Some of the common lesions are denture stomatitis, angular cheilitis, traumatic ulcers, denture irritation hyperplasia, periodontal diseases, burning mouth syndrome, flabby ridges, and oral carcinoma. 5 Other factors contributing to poor oral health along with surface roughness of the denture are inadequate oral hygiene, poor manual dexterity, failure to follow the instructions by the patients, and lack of proper instructions and guidance by the dentist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common denture cleaning practices include rinsing with tap water, brushing with toothpaste, and soaking dentures in cleansing tablets dissolved in water . When away from home, the main methods employed are rinsing under a tap or cleaning dentures with a brush and toothpaste.…”
mentioning
confidence: 99%
“…Common denture cleaning practices include rinsing with tap water, brushing with toothpaste, and soaking dentures in cleansing tablets dissolved in water. 11,12 When away from home, the main methods employed are rinsing under a tap or cleaning dentures with a brush and toothpaste. Although effective in maintaining denture cleanliness, these methods may be difficult to implement when away from the home due to the requirement for a source of water.…”
mentioning
confidence: 99%